Hubungan Pengetahuan, Sikap, dan Sosioekonomi dengan Perilaku Pencegahan Anemia pada Remaja Putri di Desa Sirnagalih, Bogor - Ayu Magdalena Natalia Situmeang; Apriningsih Apriningsih; Feda Anisah Makkiyah; Widayani Wahyuningtyas (LPPM Hang Tuah Pekanbaru, 2022)
The coexistence of anemia is widespread in low-middle income countries, and several contributing factors include poverty, limited knowledge related to anemia prevention, and inadequate nutrient intake. This study aims to study and discover the relationship of knowledge, attitudes, and socioeconomic status with efforts to prevent iron nutrition anemia in young women in Sirnagalih Village, Bogor. This research is quantitative research with the design of a cross-sectional study using primary data. The population in this research is a young woman in Sirnagalih Village who is 10-19 years old and has been menstruating. The sample selection method used in research is the “quota sampling” technique with 72 people as subjects. The data analysis was conducted with univariate tests to describe sociodemographic characteristics, knowledge, attitudes, and behaviors related to anemia prevention in adolescent girls, bivariate tests with Chi-squares, and multivariate tests using logistic regression. It was found that the level of knowledge and attitudes of adolescent girls towards anemia in Sirnagalih village is still quite low. The results found that variables related to anemia prevention behavior are knowledge (p-value 0.005), attitude (p-value 0.021), and family income (0.021). The results of the multivariate analysis revealed that family income was the most influential independent variable, with a POR value of 12,068 (95% CI 2,447–59,523; p = 0.002). Besides the income variable, there were knowledge and attitude variables that correlated with adolescent girls' preventive behavior. So, there is a need for cross-sectoral efforts to increase family income and the role of community health care in increasing the knowledge and attitudes of adolescents through promotional education related to anemia prevention.